Osteochondral tissue engineering in translational practice: histological assessments and scoring systems - Cui, Mengying; Sun, Yang; Zhang, Xiaoyang; Yang, Pengju; Jiang, Weibo (Frontiers in Bioengineering and Biotechnology, 2024)
Osteochondral lesions are common pathological alternations in synovial joints. Different techniques have been designed to achieve osteochondral repair, and tissue-engineered osteochondral grafts have shown the most promise. Histological assessments and related scoring systems are crucial for evaluating the quality of regenerated tissue, and the interpretation and comparison of various repair techniques require the establishment of a reliable and widely acceptknowledged histological method is fundamental for interpreting and comparing various repair techniques. To date, there is still no consensus on the type of histological assessment and scoring system that should be used for osteochondral repair. In this review, we summarized common osteochondral staining methods, discussed the criteria regarding high-quality histological images, and assessed the current histological scoring systems for osteochondral regeneration.Safranin O/Fast green is the most widely used staining method for the cartilage layer, whereas Gomori Staining and Van Giebson staining detect new bone formation. We suggest including the graft--host interface and more sections together with the basic histological information for images. An ideal scoring system should analyze both the cartilage and bone regions, especially for the subchondral bone plate. Furthermore, histological assessments should be performed over a longer period of time to minimize discrepancies caused by defect size and animal species.